2004
DOI: 10.2466/pr0.94.1.83-103
|View full text |Cite
|
Sign up to set email alerts
|

Ryff's Psychological Well-Being Inventory: Factorial Structure and Life History Correlates among Japanese University Students

Abstract: The theoretical model of psychological well-being that encompasses six domains (self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth) was tested with a Japanese university student population (N = 574) using a Japanese translation of Ryff's 1989 Psychological Well-being Inventory. A factor structure similar to Ryff's original model emerged. Both depression and anxiety correlated only moderately with scores on some subscales of the inventory, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 30 publications
5
41
0
3
Order By: Relevance
“…Previous studies showed significant correlations between psychological distress, depression, and anxiety with psychological well-being [5][6][7]. The results of this study support the findings of previous studies [43][44][45][46].…”
Section: Depressionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies showed significant correlations between psychological distress, depression, and anxiety with psychological well-being [5][6][7]. The results of this study support the findings of previous studies [43][44][45][46].…”
Section: Depressionsupporting
confidence: 83%
“…Nurses often account for the largest percentage of the clinical workforce [2] and their psychological well-being can impact upon the patients [3,4]. There are significant correlations between psychological distress, depression, anxiety and psychological well-being [5][6][7]. Therefore, it is an important topic to understand what factors influence nurses' psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In a Japanese context, PWB was negatively correlated with anxiety and depression among undergraduate students (Kitamura et al 2004;Liu et al 2009). These findings indirectly support the buffering hypothesis that those low in PWB may be at risk of developing emotional disorders.…”
Section: Pwb As Resilience To Anxiety Symptoms: the Buffering Hypothesismentioning
confidence: 99%
“…PWB was featured in the 1995 National Survey of Midlife Development in the U.S. (MIDUS; MIDUS II data collection in progress since 2002). In addition, PWB has been examined cross-culturally and has been translated into multiple languages including Swedish (Lindfors, Berntsson, & Lundberg, 2006), Greek (Vleioras & Bosma, 2005), Japanese (Kitamura, Kishida, Gatayama, Matsuoka, Miura & Yamabe, 2004), Chinese (Cheng & Chan, 2005), and Italian (Ruini, Ottolini, Rafanelli, Ryff, & Fava, 2003). In sum, PWB is a measure pervasively used in various domains and across age and culture.…”
mentioning
confidence: 99%